2010
DOI: 10.1021/jp1069412
|View full text |Cite
|
Sign up to set email alerts
|

Melting in 2D Lennard-Jones Systems: What Type of Phase Transition?

Abstract: A typical configuration of an equilibrium 2D system of 2500 Lennard-Jones particles at melting is found to be a mosaic of crystallites and amorphous clusters. This mosaic significantly changed at times around the period τ of local vibrations, while most particles retain their nearest neighbors for times much longer than τ. In a system of 2500 particles, we found no phase separation for length scales larger than that of a crystallite. With decreasing density, the number of small amorphous clusters increased, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…All methods yield T * ≈ 1.0 for both the GM and the 1C systems (at the same density as in the present work). The precise nature of this transition is still controversial even for 1C systems and may be affected by finite size effects [23,24]. Both the static and the dynamic properties of the GM and 1C systems are expected to be quite similar for T T * and differences between the two systems become significant as the temperature is decreased, approaching the upper limit ( ij = 4) of pair interaction parameter values in the GM system, and neighborhood identity ordering becomes increasingly important (there is no NIO in the 1C system).…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
“…All methods yield T * ≈ 1.0 for both the GM and the 1C systems (at the same density as in the present work). The precise nature of this transition is still controversial even for 1C systems and may be affected by finite size effects [23,24]. Both the static and the dynamic properties of the GM and 1C systems are expected to be quite similar for T T * and differences between the two systems become significant as the temperature is decreased, approaching the upper limit ( ij = 4) of pair interaction parameter values in the GM system, and neighborhood identity ordering becomes increasingly important (there is no NIO in the 1C system).…”
Section: Model and Simulation Detailsmentioning
confidence: 99%
“…These clusters are larger in E than in U and while the latter are compact, the E clusters are ramified with a fractal dimension of about 1.8 (Figs. [12][13][14]. Both U and E clusters are stabilized by the fact that each particle in the bulk of a compact solid-like cluster is confined to a "cage" formed by its neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies of supercooled [11] and equilibrium two-dimensional (2D) Lennard-Jones liquids [12,13] found that properties of these liquids substantially differ from their 3D-analogs. Computer simulations [12], [13], [16][17][18] confirm the assumption of the theory [14,15] that very close to the melting point 2D liquids represent a locally crystalline matrix with some concentration of spatially isolated islands of disorder around dislocations. On further increase of the temperature, these islands gradually increase in size and number, and at some temperatures percolate creating a mosaic of crystalline and non-crystalline clusters.…”
mentioning
confidence: 88%
“…the cut-off length was r cutoff =2.5. The form (1) of the interaction potential introduces natural units of length, energy, and particles number density ρ; the natural unit of temperature T coincides with that of energy (the Boltzmann constant k B =1) [13,15]. Equilibrium states along the super-critical isotherm T = 0.700 were simulated in the range of densities ρ = 0.60-0.90 that includes both the crystalline states at high-density end and non-mosaic liquid states at lowest densities.…”
mentioning
confidence: 99%
See 1 more Smart Citation